The Relationship Between Shift Work Patterns and Cognitive Function Disorders in Health Workers at Hospital X, West Java, Indonesia - Malau, Bintang Leonard; Amilya Agustina; Pukovisa Prawiroharjo; Winnugroho Wiratman; Retno Asti Werdhani (Sriwijaya Journal of Neurology, 2024)
Introduction: Jobs with shift work patterns, especially irregular ones, can disrupt circadian rhythms and sleep quality, which then impacts cognitive function. Despite its importance, research on cognitive domain vulnerabilities related to shift work patterns is still limited. Sleep quality and cognitive function are critical in the context of hospital health services, where decisions and actions must be taken quickly and precisely to support patient safety. Methods: This research is a cross-sectional observational analytical study to determine the relationship between shift work patterns and impaired cognitive function. To measure sleep quality, the Pittsburgh Sleep Quality Index Indonesian (PSQI-Ina) is used, while cognitive function and cognitive domains were measured using Oxford Cognitive Screen (OCS) Indonesian (OCS-Ina), a cognitive instrument for stroke patients, which has been validated. The minimum sample size in this study was 72 samples. Correlation, principal component analysis, demographic analysis, and regression were used to characterize the relationship between PSQI-Ina, OCS-Ina, and other research variables. Results: A total of 83 health workers met the inclusion criteria and were included in the research. The results showed that 16 respondents (19.3%) experienced impaired cognitive function in the Attention domain and 2 respondents (2.4%) experienced impairment in 2 cognitive domains (Attention and Number Management). The results of statistical analysis showed a significant relationship with health workers who had part-time jobs having a 12.8-fold risk (OR 12.8; 95% CI 1.7-91; p = 0.011) of experiencing cognitive impairment. Then health workers who experience poor sleep quality (with a PSQI value >5) have a 40.3 times greater risk (OR 40.3; 95% CI 2.2-708.1; p = 0.011) of experiencing cognitive impairment. Likewise, health workers with irregular shift work patterns have a 5.4 times risk of experiencing cognitive impairment (OR 5.4; 95% CI 0.1-26.6; p = 0.036). Conclusion: There is a relationship between shift work patterns and impaired cognitive function in the workplace. Hospitals should prioritize ergonomic shift work schedules, emphasizing speed and clockwise rotation, to support the well-being of their healthcare workers.